The International Editorship of Freshwater Systems - Karl E. Havens (The Scientific World Journal)
It is my pleasure to announce that two distinguished internationalscientists have joined the editorship of the FreshwaterSystems domain of TheScientificWorldJOURNAL Professor BrijGopal of Jawaharlal Nehru University (India) and Dr. Manual Gra柠of the Universityof Coimbra (Portugal). Professor Gopal is the Secretary General of the NationalInstitute of Ecology, Editor of the InternationalJournal of Ecology & Environmental Science,and Chairman of the SIL (International Association of Theoretical and AppliedLimnology) Committee on Limnology in Developing Countries. His research interestsinclude the ecology, biogeochemistry and biodiversity of wetland ecosystems,the management of wetlands as an integral part of the watershed, and wetlandwater policyrelated issues. Dr. Gra柠is a stream ecologist whose researchinterests include the two general areas of organic matter decomposition andbiological monitoring. His specific areas of research focus include quantificationof organic matter and other chemical changes in decomposing leaves, the ecologyof aquatic hyphomycetes, and the ecology of animals feeding on detritus. Hisresearch dealing with biological monitoring is carried out in close cooperationwith the paper and mining industries, facilitating the practical applicationof his work.